Evaluación de la metodología aplicada al modelo de evaluación de desempeño de la Dirección Regional de Trabajo y Servicio Público de Loja “Ministerio del Trabajo” año 2014. - Montero Romero, Elizabeth Noemí (2015)
This paper is the presentation of the evaluation of the methodology applied to the Performance Evaluation Model of the Regional Directorate of Labour and Public Service of Loja "Ministry of Labour" Year 2014. It seeks to determine whether the current application of Form MRL-EVAL -01-MODIFIED is right to measure operational effectiveness, efficiency and good service provided to users. It is considered to develop a new model that is a guide to performance evaluations in the public sector, suggested a function to search an assessment of overall performance and will be held at the Regional Directorate of Labour and Public Service of Loja, in order to improve the performance evaluation process servers to this list performance evaluation methods that could be applied, it is suggested the issue of performance evaluation 360 is analyzed. This assessment would not only above, plus the would perform internal and external users, coworkers or peers, subordinates, and could apply self-evaluation. KEYWORDS: Performance assessment, diagnosis, efficiency, effectiveness, organization, public servants, model.